Upaya Guru dalam Meningkatkan Kecerdasan Sosial Siswa Kelas VI Madrasah Ibtidaiyah Swasta Ma’had Al-Zaytun dalam Konteks Pembelajaran - Fauziah Nur Hidayati; Henri Peranginangin Tanjung; Dadan Mardani (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Humans are social beings, and thus they need interaction with others. Interacting requires social intelligence which is the ability to understand and express feelings to people around them. However, there are still students who are not able to interact well with the teacher. The students are unable to express their condition when they are not feeling well.The purpose of this study is to understand teachers’ efforts to improve the social intelligence of sixth-grade students at Private Islamic Primary Boarding School or Madrasah Ibtidaiyah Swasta Ma'had Al-Zaytun in the context of learning. Secondly, the study aims to identify the inhibiting and supporting factors of students’ social intelligence enhancement in learning process. This study uses a descriptive qualitative approach. To collect data, the researcher employs observation, interview, and documentation techniques. The population of this study are the sixth-grade teachers at school. Random sampling teachnique is conducted to find the sample. The samples are homeroom teacher and a subject teacher in class VI B03 and another subject teacher in class VI B07. The obstacle in this process includes lecture-based teaching, which is less interactive. This obstacle is solved by incorporating question-and-answer sessions to enable more active participation from students. The second obstacle is the use of students inappropriate language which is overcome through teacher’s consistent guidance and correction to foster better communication.